(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Coronary angiography is traditionally performed through transfemoral access. Transradial access is increasingly being used for this purpose for its various advantages. However, its use in Bangladesh is less well studied. The aim of this study was to find out the safety and efficacy of transradial access as compared to transfemoral access. Methods: This was a single-center, cross-sectional study. 100 randomly selected elective coronary angiography from August 2017 to September 2018 by the same operator using either transradial access or transfemoral access were analyzed. Results: Among 100 coronary angiography, transradial access were 50 and transfemoral access were 50. Fluoroscopy time was 3.08[1-9] vs 1.47 [1-17] minutes (p=.014), dose area product was 4807 [1947-11489] vs 3202 [1130-12826] ìGy.m2 (P<0.001), total dose was 788 [276-2055] vs 520 [158-2424] mGy (p<0.001). Transradial failure occurred in 4 (8%) cases. Transfemoral failure occurred in 1 (2%) case. There was no significant difference in failure rate between the groups (p= 0.169). Ecchymosis was the commonest (10% in transradial access vs 22% in transfemoral access, p= 0.102) among post procedure complications. Other complications like thrombophlebitis (6% vs 18%, p=0.004); hematoma (0% vs 12%, p= 0.005); puncture site bleed (2% vs 4%, p= 0. 039) were seen in TRA and transfemoral access, respectively. Conclusion: Access site complications are more in transfemoral access. Transradial access is an effective alternative to transfemoral access, and it can be performed safely by experienced operators. J Bangladesh Coll Phys Surg 2022; 40: 93-98